Bioethics in tissue engineering in the Muslim world - Sha'ban, Munirah (2010)
The multidisciplinary field of tissue-engineering was born as a means to restore or replace diseased tissue with new living tissue that is designed or constructed to meet the needs of each individual patient. Scientific advances in biomaterials, stem cells,growth factors, and biomimetic environments have created opportunities to reconstruct tissues from combinations of engineered scaffolds, cells and biologically active signaling molecules. Accordingly, advanced developments in tissue-engineering have yielded a novel set of engineered tissue implants and treatment approaches. The demand for these tissue-engineered products may increase significantly, but, the progress has been slow due to scientific and technical difficulties that subject to a wide variety of philosophical, religious and ethical challenges, and economic viewpoints. One major concern is that, there are on-going debates on certain aspects that seem to indicate that man may be playing God. On the other hand, Islam encourages seeking remedy and treatment as the Prophet SAW is reported to have said: “There is a cure for every illness, though we may not know it yet” [Al-Bukhari]. Therefore, deliberations on tissue-engineering must include the religious and ethical perspectives since there are still many grey areas that require the Islamic input. Religious and ethical discourses should be initiated between scientists, ethicist and Islamic scholars (ulama’) since we are lacking of Islamic establishment in the area of bioethics in local and global community. In terms of basis of Islamic society, there is a need for discussion; ijtihad is a concept which gives flexibility to examine and adopt new scientific developments and resolve issues in the light of two major sources of Islam; the Al-Qur’an and As-Sunnah. Through the discussion, tissue-engineer scientists would be able to constantly enlighten ulama’ on the technology developments, whilst ulama’ could convey the essential Islamic input on each aspect of developments. Hence, it is clearly significant that ulama’ must first understand tissue-engineering technology and its’ processes. The outcome of the discussion will indeed influence tissue engineering progress; the conditions for its acceptance or the grounds for its rejection. Eventually, it is the general society who will benefit the most from this scholarly ‘win-win’ meeting of minds.